1971
DOI: 10.1029/rg009i001p00027
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of cosmic rays in the solar wind

Abstract: This paper presents a coherent exposition of the modern statistical theory of the transport of fast charged particles (cosmic rays) in the solar wind. Observations are discussed only as they illustrate the phenomena under discussion. A brief introductory section surveys the historical development of the theory. The dominant effect on the motion of cosmic rays in the solar wind is the interplanetary magnetic field, which is irregular and which is therefore best treated statistically, using random functions. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
298
0

Year Published

1978
1978
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 512 publications
(306 citation statements)
references
References 105 publications
8
298
0
Order By: Relevance
“…This implies that the radial diffusion coefficient is directly proportional to particle rigidity (R) for transient modulation for positive as well as negative cycles over a large range of rigidities. This rules out the existence of a ''transition rigidity'' suggested by Jokipii [1971] even for a short-term modulation. At this point, one should also note that Lockwood and Webber [1967] compute R m values in an ad hoc manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that the radial diffusion coefficient is directly proportional to particle rigidity (R) for transient modulation for positive as well as negative cycles over a large range of rigidities. This rules out the existence of a ''transition rigidity'' suggested by Jokipii [1971] even for a short-term modulation. At this point, one should also note that Lockwood and Webber [1967] compute R m values in an ad hoc manner.…”
Section: Discussionmentioning
confidence: 99%
“…[19] Sometime ago, Jokipii [1971] proposed a diffusion theory of cosmic ray modulation and used it to deduce the rigidity (R) dependence of the diffusion coefficient (k) in IMF, at the Earth's orbit. He used the measured magnetic field power spectra in space and concluded that the dependence changes from k / R 0.5 to k / R 2 , at R $ 2 GV (termed transition rigidity).…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that they play the role of scattering centers for the particles, producing a spatial gradient in' cosmic ray intensities as well as a modulation with solar.activity (see reviews by Jokipii, 1971;vblk, 1975b;Moraa, 1976). The radial variation of magnetic field fluctuations causes a corresponding variation of the particle diffusion, with an obvious beafng ofxithh&_avie-ifht of models of particle propagation.…”
Section: ~1 6mentioning
confidence: 99%
“…Most models of this propagation up to the quasilinear approximation assume that to zeroth order such particles follow a helical orbit along the mean spiral field while undergoing some spatial diffusion due to the effects of field fluctuations (Jokipii, 1971;Vlk, 1975a,b)° Recent nonlinear approaches (V61k, 1975b;Goldstein, 1976;Jones et al, 1977) and the local approximation quasilinear approach of Klimas et al (1976a,b; seek to remedy the inability of previous theories to accurately describe the more complex motions of cosmic ray particles with large (near 900) pitch angles and/or moderate to strong magnetic turbulence. There have been several attempts to determine the radial distance dependence of the cosmic ray diffusion tensor (Jokipii, 1973;V6Ik et al, 1974), but these have relied heavily on theoretical models for the spatial dependence of the magnetic spectrum which.may not correspond to the real situation (V5lk, 1975b).…”
mentioning
confidence: 99%
“…We assume a well-developed magnetic turbulence with a Kolmogorov power spectrum P∝k −5/3 in the coronal region. κ P can be calculated from the quasilinear theory (Jokipii 1971). The resulting diffusion coefficient has a momentum dependence, κ P ∝p 4/3 , when the particle gyroradius is much smaller than the correlation length of turbulence.…”
Section: Particle Accelerationmentioning
confidence: 99%